The Great ReckoningThe Great Reckoning, by DavidsonJames Dale and Rees-MoggLord William. New York: Simon & Schuster, 1993, 607 pp., $23.00, ISBN: 0-671-86994-9. - Gaston, Leonard (Academy of Management Review, 1994)
The article reviews the book ?The Great Reckoning,? by James Dale Davidson and Lord William Rees-Mogg.